2021
DOI: 10.1158/1538-7445.am2021-lb071
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB071: Tuning the tumor myeloid microenvironment (TME) by targeting TREM2+ tumor-associated macrophages to overcome resistance to immune checkpoint inhibitors

Abstract: The tumor microenvironment (TME) often contains high levels of suppressive myeloid cells that may contribute to innate checkpoint inhibitor (CPI) resistance. Pionyr's Myeloid Tuning approach involves altering the composition and/or the function of myeloid cells in the TME. To this end, therapeutic targeting of tumor-associated macrophages (TAMs) is a promising strategy to increase CPI response rates in solid tumor indications, as well as to overcome resistance to CPI therapies. Pionyr and others identified the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Finally, the level of TREM2 presence within TAMs has been positively correlated with tumor staging, including the degree of nodal metastases. Similar inverse trends of TREM2 expression and overall survival have been documented with gastric, hepatic, colorectal, ovarian and breast cancers [ 411 , 413 , 414 ]. Other studies utilizing TREM2 −/− mice and TREM2 inhibitors for sarcoma, colorectal, and breast cancer models have demonstrated that TREM2 deficiency leads to improved antigen presentation from TREM2 −/− macrophages compared to wild type, along with improved CD8 + TIL presence and PD-1 expression, suggesting that TREM2 inhibition may be synergistic with ICI therapy [ 411 ].…”
Section: Emerging Targets For Therapeutic Manipulation Of Myeloid Cellssupporting
confidence: 66%
See 1 more Smart Citation
“…Finally, the level of TREM2 presence within TAMs has been positively correlated with tumor staging, including the degree of nodal metastases. Similar inverse trends of TREM2 expression and overall survival have been documented with gastric, hepatic, colorectal, ovarian and breast cancers [ 411 , 413 , 414 ]. Other studies utilizing TREM2 −/− mice and TREM2 inhibitors for sarcoma, colorectal, and breast cancer models have demonstrated that TREM2 deficiency leads to improved antigen presentation from TREM2 −/− macrophages compared to wild type, along with improved CD8 + TIL presence and PD-1 expression, suggesting that TREM2 inhibition may be synergistic with ICI therapy [ 411 ].…”
Section: Emerging Targets For Therapeutic Manipulation Of Myeloid Cellssupporting
confidence: 66%
“…PY314, a humanized monoclonal antibody against TREM2, was among the first to reach clinical trials, with a phase I study (NCT04691375) currently underway comparing PY314 therapy with or without pembrolizumab in patients with advanced solid tumors. While clinical data are currently ongoing, preclinical studies involving PY314 have demonstrated that this anti-TREM2 therapy can provide anti-tumor activity in certain breast cancer models (EMT6) while improving the immune landscape of the TME through increasing the presence of CD8 + TILs, NK cells, and MHC-II-expressing TAMs [ 413 ]. When combined with anti-PD-L1, PY314 further amplifies these immune cell changes, as seen via flow cytometry and IHC staining.…”
Section: Emerging Targets For Therapeutic Manipulation Of Myeloid Cellsmentioning
confidence: 99%
“…Preclinical studies of PY314 have shown antitumor effects of anti-TREM2 therapy in breast cancer. This may be because PY314 reduces the infiltration of pro-tumorigenic M2 phenotype macrophages, while increasing the infiltration of CD8 + T cells, NK cells and M1 phenotype macrophages [ 71 ]. Numerous interventions are possible to block TREM2 and its related signaling pathway, such as blocking the extracellular domain with a specific monoclonal antibody (mAb), deleting TREM2 ligands that conditionally existed in the tumor or directly inhibiting TREM2 downstream molecules involved in a related signaling pathway.…”
Section: Discussionmentioning
confidence: 99%